Research Note: Transcriptome analysis of skeletal muscles of black-boned chickens, including 2 types (wild and mutated) of Taihe black-boned silky fowl and 1 type (wild) of Yugan black-boned chicken - Cong Huang; Yue Wei; Zhaofeng Kang; Weihong Zhang; Yanping Wu (Poultry Science, 2024)
ABSTRACT: The large amount of melanin deposited in Taihe black-boned silky fowl and other black-boned chicken breeds is a highly valued trait due to its desirable nutritional and functional properties, such as antiaging, immune-enhancing, and antifatigue properties. To identify the candidate genes and pathways potentially responsible for melanogenesis in Taihe black-boned silky fowl, digital gene expression tag (DGE-tag)-based transcriptome analyses were performed for 2 groups: wild-type Taihe black-boned silky fowl (TH-1245) vs. mutated Taihe black-boned silky fowl (BY-1245) and TH-1245 vs. wild-type Yugan black-boned chicken (YG-1245). In total, 430 and 765 differentially expressed genes (DEGs) were identified and 13 DEGs displaying different gene expression patterns between the 2 groups were considered valuable for further investigation, such as ANKRD1, MYOZ2, and MYOD1. Furthermore, 6 functionally grouped networks composed of 36 significant GO terms, mainly involved in muscle-related and signaling-related biological processes, were screened by functional enrichment network analysis. In addition, protein–protein interaction (PPI) network analysis identifies 2 top clusters containing 20 hub genes for 2 comparison groups. MYL1 and RPS14 were considered the most potential candidate genes among all hub genes. The Gene Set Enrichment Analysis (GSEA) results showed that the terms and pathways, such as muscle system process, arachidonic acid metabolism, melanogenesis, and tyrosine metabolism, may play important roles in the melanogenesis and further investigations were needed to clarify the relationships between these pathways and melanin. Overall, these results are helpful for furthering our understanding of melanogenesis in breast muscle of Taihe black-boned silky fowl and Yugan black-boned chicken.